Corporate Governance, Profitability, Dividends: Impact on Earnings Management: Dampak Tata Kelola Perusahaan, Profitabilitas, dan Kebijakan Dividen pada Manajemen Laba di Perusahaan Manufaktur: Analisis Kuantitatif - Muhammad Sabdo Sartam; Wisnu Panggah Setiyono (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to examine the influence of good corporate governance, profitability, and dividend policy on earnings management in manufacturing companies within the consumption sector during the period 2015-2019. Employing a quantitative approach, the study used purposive sampling to select a sample of nine manufacturing companies, resulting in the analysis of 45 financial statements. The data was analyzed using multiple linear regression through the SPSS version 25 program. The findings reveal that good corporate governance does not significantly affect earnings management, while profitability exhibits a significant impact. Moreover, dividend policy does not have a significant effect on earnings management. However, collectively, good corporate governance, profitability, and dividend policy significantly influence earnings management. These results contribute to the existing literature on corporate governance and provide implications for stakeholders, including regulators, investors, and management, in their efforts to enhance financial performance and minimize earnings management practices in manufacturing companies. Highlights: The study examines the influence of corporate governance, profitability, and dividend policy on earnings management in manufacturing companies. Profitability demonstrates a significant impact on earnings management. Good corporate governance and dividend policy do not individually have a significant effect on earnings management, but collectively they show a significant influence. Keywords: Corporate Governance, Profitability, Dividend Policy, Earnings Management, Manufacturing Companies.